2018
DOI: 10.2147/ott.s163163
|View full text |Cite
|
Sign up to set email alerts
|

<em>TRIM44</em>, a crucial target of miR-410, functions as a potential oncogene in osteosarcoma

Abstract: PurposeMounting evidence highlights the essential role of TRIM44 in tumor initiation and malignant progression in several cancers; however, the function of TRIM44 in osteosarcoma (OS) remains unknown. In this study, we aim to investigate the role of TRIM44 and reveal its regulation by deregulated miRNAs in OS.Materials and methodsThe expression profiles of TRIM44 were examined by immunohistochemistry, Western blotting, and qRT-PCR. The biological functions of TRIM44 were investigated through siRNA-mediated kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…Tripartite motif 44 (TRIM44) is a TRIM family protein that is involved in the ubiquitination and degradation of target proteins by modulating E3 ubiquitin ligases. It has been reported that TRIM44 is overexpressed in various pathological conditions, including developmental disorders, as well as in cell cycle regulation and DNA damage responses 24 . Previous reports have revealed that TRIM functions as a marker for the degradation of target proteins through the proteasome, but it also regulates protein-protein interactions and enzyme activation 25,26 .…”
mentioning
confidence: 99%
“…Tripartite motif 44 (TRIM44) is a TRIM family protein that is involved in the ubiquitination and degradation of target proteins by modulating E3 ubiquitin ligases. It has been reported that TRIM44 is overexpressed in various pathological conditions, including developmental disorders, as well as in cell cycle regulation and DNA damage responses 24 . Previous reports have revealed that TRIM functions as a marker for the degradation of target proteins through the proteasome, but it also regulates protein-protein interactions and enzyme activation 25,26 .…”
mentioning
confidence: 99%
“…1. After further discussion and consideration of the selected articles, 13 cohort studies published between 2012 and 2019 were selected for further analysis [9,10,[26][27][28][29][30][31][32][33][34][35][36]. In total, these 13 studies included 1740 patients with a mean sample size of 133.8 and a range from 68 to 331.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Study collection and screening process are shown in Figure 1. After further discussion and consideration of the selected articles, 13 cohort studies published between 2012 and 2019 were selected for further analysis [9,10,[26][27][28][29][30][31][32][33][34][35][36]. In total, these 13 studies included 1,740 patients with a mean sample size of 133.8 and a range from 68 to 331.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%